Dynamic Polarization Converter Using a Polymer-Based Plasmonic Metasurface - Muhammad Saad Asad; Muhammad Zulfiker Alam (IEEE Access)
Control of polarization is vital for many applications of photonics including sensing, communication, imaging and quantum optics. Currently available components for polarization control are often bulky and static, which limits their applications. Active metasurfaces offer a new way of achieving dynamic control of polarization with greater flexibility. We propose the design of a polymer based plasmonic metasurface to control the polarization state of the reflected light. By adjusting the temperature of the metasurface, it is possible to convert linearly polarized light to left or right handed circularly polarized light with more than 80% efficiency. It can also achieve co-polarization to cross-polarization conversion with 33% efficiency and a wide range of linear to elliptical polarization conversion. We also presented a design for THz region which provides good performance. The combination of high efficiency, large range of achievable polarization states and flexible fabrication process can make the proposed device useful for a wide range of applications. We believe this work will encourage further developments of active metasurface devices which utilize thermo-optic effect in polymers for achieving amplitude and phase tunability.